Konversi Kayu Ketapang (Terminalia Catappa. L) Menjadi Bio-Oil Menggunakan Metode Pirolisis Dengan Katalis Co-Mo/NZA - Rizky, Muhammad; Bahri, Syaiful; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The demand of fossil fuel  is increasing each year. On the other hand,  the availability of conventional petroleum fuels diminishing due to its non-renewable. Therefore, it is necessary to develop  a  new alternative  fuel  that can be renewed,  one of the solution  is the  processing of biomass into bio-oil. Bio-oil is a result of the pyrolysis of biomass. Availability of Ketapang rod is converted  into bio-oil by pyrolysis method using catalysts natural zeolite. The purpose of this study was  to  determine the performance of  the catalyst  to  produce bio-oil,  characterize  the density, viscosity, acid number, and flash point of bio-oil  that produced, as well as analyze  the chemical components  of bio-oil  by GC-MS method.  Pyrolysis of  Ketapang rod  catalyst  from natural zeolite  in the reactor  slurry  do  by feeding 50 grams with the size    -100 +200 mesh, silinap 500 ml, stirring speed is set to 300 rpm, 320oC temperature, and the process runs for 120 minutes. The results showed that the optimum yield obtained  on 2.5% catalyst, amounting to 77%. The test results obtained by the physical properties of density 0.875 g/ml, 9.56  cSt viscosity, acid number of 49,89 gr NaOH/gr sample. Keywords: Bio-oil, pyrolysis, Ketapang rod, natural zeolite, alternative fuels